Development of Comic-Based Distance Learning Module in Islamic Religious Education Subjects - Muhammad Sinar Randi; Siti Halimah; Salamuddin Salamuddin (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to analyze and develop a comic-based distance learning module (PJJ) in PAI Class V subjects at SDIT DOD Medan. This study uses a research and development (RnD) approach with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data collection instruments in this study, namely observation, interviews, questionnaires, and documentation. The results of this study indicate that (1) the feasibility of the comic-based PJJ module was validated by material experts with the acquisition of a percentage of 66.25% in the valid category, validation by media experts obtained a percentage of 78.75% also in the valid category and validation from teachers of religious education subjects. Islam SDIT DOD Medan obtained a percentage of 86.67% in the very valid category, so the overall average value of the percentage is 77.22% with a valid category; (2) the practicality of the comic-based PJJ module obtained an overall average score of 83.67% in the very practical category; and (3) the effectiveness of the PJJ module on Islamic Religious Education subjects in improving student learning outcomes obtained a normalized gain (N-Gain) score of 0.52, which is in the effective category. So it can be concluded that the product of developing comic-based distance learning modules in Islamic Religious Education subjects is effective in increasing student learning outcomes.